BUSINESS RESEARCH METHODS - MISHRA PRAHLAD (NEW DELHI OXFORD UNIVERSITY PRESS, 2022)
"Business Research Methods" by Dr. Prahlad Mishra is a comprehensive textbook designed to equip postgraduate management students and young professionals with the essential knowledge and skills to conduct systematic research in a business context. The book meticulously covers the entire research lifecycle, from conceptualization to reporting, with a strong emphasis on practical application and data analysis. It stands out for its clear, accessible language and its integration of popular statistical software like SPSS and Excel.
RESEARCH METHODS
BUSINESS RESEARCH
Keywords: RESEARCH METHODLOGY; MANAGEMENT